Aplikasi Edible Coating dari Limbah Kulit Udang dengan Aditif Asap Cair untuk Kemasan Sosis Sapi Antibakteri Ramah Lingkungan - Ardhiansyah, Hanif; Radenrara Dewi Artanti Putri; Catur Rini Widyastuti; Widi Astuti; Negoro, Gusti Maulana; Situmorang, Monatalia Lamtama; Hamid, Delvani Putri Faradilla (Jurnal Teknik Kimia USU, 2024)
Edible coating is a food preservation technique by coating using antimicrobial substances which can inhibit the growth of bacteria. This research aims to develop an edible coating from shrimp shell waste with liquid smoke additives as antibacterial packaging for processing beef sausages. Chitosan is made in three stages, namely demineralization, deproteination and deacetylation. Beef sausages coated with edible coating were tested using organoleptic and antibacterial tests. The results of this research showed that the highest degree of deacetylation of chitosan was found in the variable concentration of sodium hydroxide (NaOH) 55% with a degree of deacetylation value of 93.59%. The water and protein content in beef sausages coated with edible coating with liquid smoke showed values of 52.45% and 12.65% on the 7th day. This is in accordance with the Indonesian National Standards (SNI). Coating beef sausages using edible coating from 2% chitosan with 8% liquid smoke solvent has antimicrobial properties because in the antibacterial test a clear zone appeared on the beef sausages coated with edible coating.